Wajib Infaq untuk Pembangunan Masjid Nurul Huda di Desa Suka Jadi Kecamatan Wih Pesam Kabupaten Bener Meriah Ditinjau Mashlaẖah - Jamalwi; Kamal, Mustafa; Fitra, Khairul; Amiruddin (Ameena Journal, 2023)
The mandatory infaq program of one million rupiahs per household in Suka Jadi Village, Wih Pesam District, Bener Meriah Regency, aims to raise funds for rebuilding the Nurul Huda Mosque after an earthquake. The program sparked debates within the community, considering residents' financial capabilities and the purpose of the mosque construction. This study seeks to explore community practices and perceptions regarding the mandatory infaq and evaluate its benefits through the lens of the mashlahah theory. A qualitative method was applied with a case study and fieldwork approach. Data were collected through interviews and documentation, then analyzed using data reduction, presentation, and conclusion drawing. The findings indicate that although no sanctions are imposed on those who delay their contributions, residents still strive to donate, even over extended periods. From the mashlahah perspective, this program offers substantial benefits, particularly in terms of dharuriyyah (urgent needs). The mosque construction is deemed essential to fulfilling hifz al-din (protection of religion), supporting Islamic practices in the local community. Overall, this initiative fosters religious practice and social solidarity in Suka Jadi Village.